The Role of Public Expenditures on Community Welfare - Dosinta, Nina Febriana; Djafar, Fariastuti; Yantiana, Nella (Jurnal Economia, 2024)
AbstractThis study aims to determine whether public expenditures in meeting basic human needs affect community welfare. This study uses data on realizing the spending on education, health, and social protection as a proxy for public expenditures and the human development index for community welfare. This study indicates that education and health expenditures have a significant positive effect, while social protection expenditures have a significant negative effect. This study confirms disclosures in the Audit Report of the Audit Board of the Republic of Indonesia. The disclosures in Provincial Government Financial Statements in Indonesia state that the regional government prioritized meeting basic needs, education, health, and social on mandatory spending to improve the quality of community life. This research implies that social protection expenditure is not optimal for developing human capabilities. Keywords:Education Expenditure, Health Expenditure, Social Protection Expenditure, Human   Capability, Community Welfare